الفكر التربوي والرؤية الاسلامية الكونية عند أبي حامد الغزالي - بوساحة, بشير; فرطاس, إيمان (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة لإبراز الفكر التربوي عند أبي حامد الغزالي، والأسس التي يقوم عليها، ومدى قدرته على رسم وترسيخ الرؤية الكونية التوحيدية الاسلامية في أذهان النشأ، لتحقيق النجاح على مستوى الفرد والمجتمع، وتحصيل السعادة في الدنيا والآخرة. وخلصت هذه الدراسة إلى أن الفكر التربوي عند الغزالي يقوم على رؤية كونية تجمع بين اتجاه الفقهاء والمتكلمة الذين نظروا للكون من داخله وعلاقته بالإنسان، واتجاه المتصوفة الذي يرى الكون من خارجه، انطلاقا مما يريده الله من الكون والانسان معا، كما أن هذا الفكر التربوي يجمع بين العبودية ومعرفة الله، والسعي لتحقيق الرقي والكمال في الحياة الاجتماعية من خلال عملية تربوية وتعليمية متكاملة. Abstract: This study aims to highlight the educational thought of Abu Hamid Al-Ghazali, the foundations on which it is based, and the extent of his ability to draw and consolidate the monotheistic Islamic cosmic vision in the minds of young people, to realize success at the level of the individual and society, and the achievement of happiness in this world and the hereafter. This study concluded that the educational thought of Al-Ghazali is based on a cosmic vision that combines the direction of the jurists and theologians who looked at the universe from within and its relationship with man, and the direction of the Sufis who see the universe from outside, based on what God wants from the universe and man together, and this educational thought combines between Bondage and knowledge of God, and the pursuit of progress and perfection in social life through an integrated educational and educational process.
مقال
Keywords: ابو حامد الغزالي ; رؤية كونية ; فكر تربوي ; عملية تربوية ; تصوف; Abu Hamid Al-Ghazali; cosmic vision; educational thought; educational process; mysticism